Comparison of graft patency following coronary artery bypass grafting in the left versus the right coronary artery systems: a systematic review and meta-analysis. (28th February 2018) - Pinho-Gomes, Ana-Catarina; Azevedo, Luis; Antoniades, Charalambos; Taggart, David P
Abstract: Although coronary artery bypass grafting has been the standard of care for patients with complex coronary artery disease for over 50 years, the evolution of graft patency over time in the left versus the right coronary systems remains poorly documented. This systematic review and meta-analysis aimed to characterize the evolution of graft patency over time comparing the left (excluding left anterior descending artery) and right coronary systems, with an emphasis on the comparison of venous versus arterial grafts and symptomatic versus asymptomatic patients. We searched the Cochrane Central Register of Controlled Trials (CENTRAL) and MEDLINE from inception to August 2016. We also searched clinical trials registers and reference lists of relevant studies. We included randomized clinical trials and observational studies comparing graft patency in the left versus the right coronary systems. Our outcome was graft patency defined as a binary variable according to whether grafts were reported as patent or failed at the time of angiogram. Data collection and analysis were performed according to the methodological recommendations of the Cochrane Collaboration. From a total 2275 papers, 52 studies were included in the qualitative analysis and 48 studies (including 36 006 grafts) in the meta-analysis. There was a 3.3% significant difference between the left-sided and right-sided graft patency, and the difference appeared to increase over time. Furthermore, patency of arterial grafts was higher in the left coronary system, while venous grafts performed similarly irrespective of the coronary circulation. Symptom recurrence also seemed related to a higher failure rate in the right coronary circulation. However, the high degree of heterogeneity precluded drawing definite conclusions. This meta-analysis suggested that graft patency might be better for left-sided vessels and that this difference might be driven by the better performance of arterial grafts in the left coronary system. However, evidence currently available is limited, and further research is warranted to understand whether certain grafts achieve better patency in the right versus the left coronary circulations.